2023
DOI: 10.3389/fnins.2023.1162851
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of electrical stimulation for peripheral nerve injury: a systematic review

Abstract: IntroductionPeripheral nerve injuries are common neurologic injuries that are challenging to treat with current therapies. Electrical stimulation has been shown to accelerate reinnervation and enhance functional recovery. This study aims to review the literature on clinical application of electrical stimulation for peripheral nerve injury.MethodsPubMed and Embase were sourced from 1995 to August 2022. Selection was based on predetermined inclusion/exclusion criteria. Eight hundred and thirty-five articles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
(95 reference statements)
1
2
0
Order By: Relevance
“…Techniques such as electrical stimulation therapy have been found to promote axon growth during nerve repair and hasten sensorimotor recovery. 19,21,24,29,30,[33][34][35][110][111][112][113] A systematic review by Costello et al 114 further corroborates the potential of electrical stimulation as a beneficial nonsurgical intervention for PNIs, aligning with the diverse treatment methodologies emphasized in this review.…”
Section: Discussionsupporting
confidence: 64%
“…Techniques such as electrical stimulation therapy have been found to promote axon growth during nerve repair and hasten sensorimotor recovery. 19,21,24,29,30,[33][34][35][110][111][112][113] A systematic review by Costello et al 114 further corroborates the potential of electrical stimulation as a beneficial nonsurgical intervention for PNIs, aligning with the diverse treatment methodologies emphasized in this review.…”
Section: Discussionsupporting
confidence: 64%
“…Before comprehensively evaluating the effect of continuous microcurrent electrical nerve stimulation (cMENS) on long-distance peripheral nerve defect repair, we optimized the electrical stimulation parameters. Given the established acceptance of a frequency of 20 Hz and pulse width of 200 us for peripheral nerve injury treatment (Park et al, 2019;Costello et al, 2023), our focus was on screening stimulation intensity and duration. Stimulation intensities of 1 mA and 100 uA, along with durations of one-time 15-min and continuous 10-day, 15-min sessions, were set in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have yielded promising therapeutic outcomes, emphasizing the potential of these approaches in enhancing peripheral nerve regeneration. Among these therapeutic modalities, electrical stimulation (ES) has a long history in the field of nerve injury repair, and its clinical efficacy has gained widespread recognition (ElAbd et al, 2022;Costello et al, 2023). Previous research has demonstrated that electrical stimulation can expedite the process of Wallerian degeneration (Li et al, 2023), encourage axonal regeneration (Zuo et al, 2020), and ultimately facilitate the restoration of motor and sensory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness and technical limitations also impede ES adaptation. Furthermore, measures such as motor unit number estimation (MUNE) are currently limited to the laboratory setting, hampering their use in the clinical environment 88 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%